Why too much biomedical research is often undeserving of the public’s trust - Mark Yarborough (Frontiers in Genetics)
This article queries whether the public can be reasonably confident that the biomedical research endeavor repays the public’s trust in it with research that routinely deserves that trust. I argue below that a research endeavor that would deserve trust is one that routinely produces research whose published results are dependable, investigates socially important questions, and is conducted ethically. While various inferences can be drawn about terms like “routinely,” “dependable,” and “socially important,” I think they are still informative enough to fruitfully guide the query that follows. The query is shaped by two stipulations that are explicated further below. The first is normative: a collective endeavor that enjoys a broad range of public concessions, such as government funding, favorable public policy like patent law or tailored legal immunities, or widespread support from private philanthropy, all meant to facilitate the endeavor, ought not solicit the public’s trust that gives rise to these concessions without being confident that it deserves it. The second is that confidence requires effective and transparent accountability. The query concludes that the public cannot be reasonably confident that the biomedical research endeavor routinely repays the public’s trust in it with research that deserves that trust1. A final item of note about the query is that it does not directly engage the recent Covid pandemic. The reasons it does not are that there is already ample engagement around that episode on the one hand and, on the other, the items of concern that are addressed in the query long predate that particular pandemic and the controversies it has engendered, many of which will likely persist no matter what eventual reforms might follow from the resolution of Covid-specific controversies.